Bentuk dan Makna Tulisan Grafiti pada Tembok Pagar Bangunan Pertokoan dan Perumahan di Pasir Panjang Kota Kupang - Nenotek, Yoyarib; Djawa, Alex; Pekuwali, Dian Sari Arindah (Jurnal Lazuardi, 2025)
The focus of this research is "The Form and Meaning of Graffiti Writing on the Fence Walls of Shops and Housing Buildings in Pasir Panjang, Kupang City." The purpose of this research is to describe the form and meaning of graffiti writing on the fence walls of shops and housing buildings in Pasir Panjang, Kupang City. The theory used is Charles Sanders Pierce's semiotics, which focuses on icons, indexes, and symbols. The method used is a qualitative descriptive method. This thesis presents 18 graffiti writing data items analyzed, consisting of 4 graffiti writing data in the form of words and 14 graffiti writing data in the form of sentences. This thesis provides an in-depth explanation of graffiti writing in the form of words and sentences, as well as the deeper meaning of graffiti writing in the form of words and sentences.